On schist walls, wild boars and olive trees: landscape and dwelling in Rural Portugal - Pires, Ema (2021)
Landscape, time and dwelling are intertwi- ned categories in many depopulated places in Portugal. This chapter questions the pos- sibilities of “dwelling” in central Portugal during the current pandemic. The empi- rical focus was put on a rural parish whe- re we have been carrying out ethnographic research since 2018. Located in the district of Castelo Branco, in the municipality of Proença-a-Nova, Mó is an almost uninhabi- ted village (in 2020, it had only 3 permanent residents). In recent decades, rural exodus has been intensified by the (un)certainty of occasional fires that have devastated the region. In 2003, the village was besieged by fire and, even though the houses and human beings were spared from destruction, every- thing around Mó was turned into ashes. The pine forests surrounding the village were burnt along with many of the animals living in them. The analytical focus of this paper is, therefore, put in questioning the possi- bilities of “dwelling” in this rural hamlet of the interior of Portugal during the current pandemic. We will argue that during the current times, there has an increase in the social value given to nature by residents.